EQUALIZING THE BANK POSITION AND BUSINESSES IN CREDIT AGREEMENT WITH THE GUARANTEE OF MORTGAGE - Imanullah, Najib (Faculty of Law, Universitas Sebelas Maret, 2018)
The Security Law, which regulates the land mortgage has significance meaning to move real sector, thus it can support the development of national economy. In this case, the traders, on the one hand, need capital for business activities, while on the other side of the capital owners seek to profit from their investment. Bank as an intermediary is required to be careful. An implementation of the precautionary principle is to have collateral for loans to businesses. One of the collateral is immovable asset (land), which is secured by the Mortgage. In practice, stipulation of mortgage is still more in favor of the bank. If this is allowed, it can be conditions that would adversely affect the parties. Thus, we need to make updates Security Law that balances position of banks and businesses, which in accordance with the attitude of mutual cooperation with based on the fundamental values which are reflected in the philosophical basis of the Indonesian nation.